Protective Effect of Casperome®, an Orally Bioavailable Frankincense Extract, on Lipopolysaccharide- Induced Systemic Inflammation in Mice - Loeser, Konstantin; Seemann, Semjon; König, Stefanie; Lenhardt, Isabell; Abdel-Tawab, Mona; Koeberle, Andreas; Werz, Oliver; Lupp, Amelie (Frontiers in Pharmacology, 2018)
Introduction: Despite recent advances in critical care, sepsis remains a crucial cause of morbidity and mortality in intensive care units. Therefore, the identification of new therapeutic strategies is of great importance. Since ancient times, frankincense is used in traditional medicine for the treatment of chronic inflammatory disorders such as rheumatoid arthritis. Thus, the present study intends to evaluate if Casperome®, an orally bioavailable soy lecithine-based formulation of standardized frankincense extract, is able to ameliorate systemic effects and organ damages induced by severe systemic inflammation using a murine model of sepsis, i.e. intraperitoneal administration of lipopolysaccharides (LPS). Methods: Male 60 day-old mice were assigned to six treatment groups: (1) control, (2) LPS, (3) soy lecithin (blank lecithin without frankincense extract), (4) Casperome®, (5) soy lecithin plus LPS, or (6) Casperome® plus LPS. Soy lecithin and Casperome® were given three hours prior to LPS treatment. 24 hours after LPS administration animals were sacrificed and health status and serum cytokine levels were evaluated. Additionally, parameters representing liver damage or liver function and indicating oxidative stress in different organs were determined. Furthermore, markers for apoptosis and immune cell redistribution were assessed by immunohistochemistry in liver and spleen. Results: LPS treatment caused a decrease in body temperature, blood glucose levels, liver glycogen content and biotransformation capacity along with an increase in serum cytokine levels and oxidative stress in various organs. Additionally, apoptotic processes were increased in spleen besides a pronounced immune cell infiltration in both liver and spleen. Pretreatment with Casperome® significantly improved health status, blood glucose values and body temperature of the animals, while serum levels of pro-inflammatory cytokines and oxidative stress in all organs tested were significantly diminished. Finally, apoptotic processes in spleen, liver glycogen loss and immune cell infiltration in liver and spleen were distinctly reduced. Casperome® also appears to induce various cytochrome P450 isoforms, thus causing re-establishment of liver biotransformation capacity in LPS-treated mice. Conclusion: Casperome® displayed anti-inflammatory, anti-oxidative and hepatoprotective effects. Thus, orally bioavailable frankincense extracts may serve as a new supportive treatment option in acute systemic inflammation and accompanied liver dysfunction.